2004
DOI: 10.1097/01.ccm.0000127261.09066.6e
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of proton pump inhibitor therapy for acute peptic ulcer-related bleeding*

Abstract: High-dose intravenous PPI therapy in conjunction with therapeutic endoscopy is the most cost-effective approach for the management of hospitalized patients with acute peptic ulcer bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 41 publications
1
12
1
Order By: Relevance
“…Randomized controlled trials support the cost-effectiveness of IV PPIs in the setting of peri-endoscopic hemostasis of bleeding peptic ulcers [23][24][25][26]. However, inappropriate IV PPI prescribing habits are associated with significant additional costs.…”
Section: Discussionmentioning
confidence: 97%
“…Randomized controlled trials support the cost-effectiveness of IV PPIs in the setting of peri-endoscopic hemostasis of bleeding peptic ulcers [23][24][25][26]. However, inappropriate IV PPI prescribing habits are associated with significant additional costs.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies also demonstrated that high-dose intravenous PPI therapy in conjunction with therapeutic endoscopy is the most cost-effective approach for managing hospitalized patients with acute peptic ulcer bleeding [21,22]. Based on our study, it is unknown whether administration of continuous intravenous pantoprazole is cost effective for treating severe erosive esophagitis.…”
Section: Discussionmentioning
confidence: 86%
“…[11,52] The cost effectiveness of high-dose IV proton pump inhibitor after successful endoscopic haemostasis has also been compared with oral PPI therapy, but with conflicting results. Two studies showed that high-dose IV proton pump inhibitor therapy was the most cost-effective approach for the management of acute peptic ulcer bleeding, [40,53] but a subsequent study by Spiegel et al [54] reported that the higher effectiveness of IV therapy may not offset its increased costs compared with oral therapy. The reasons for the divergent outcomes are, in part, due to differing assumptions in management approaches and resulting base-case estimates with limited precision of the results.…”
Section: Discussionmentioning
confidence: 98%